Pilot study of the Sensory Over-Responsivity Scales: assessment and inventory. - Schoen SA; Miller LJ; Green KE (American Journal of Occupational Therapy)
This article describes 3 stages of construction of the Sensory Over-Responsivity (SensOR) Scales: instrument development, reliability and validity analyses, and cross-validation on a new sample. The SensOR Scales include the SensOR Assessment, an examiner-administered performance evaluation, and the SensOR Inventory, a caregiver self-rating scale. Both scales measure sensory overresponsivity in 7 sensory domains. Data were collected from 2 samples consisting of participants who were typically developing (ns = 60 and 44, respectively) and participants with sensory overresponsivity (ns = 65 and 48, respectively), ages 3 to 55. In developing the research edition, items on the pilot version were reviewed for their internal consistency reliability, discriminant validity, and construct validity. Data from both samples on the research edition revealed high internal consistency reliability for domains and the total test and significant discrimination between the overresponsive and the typically responsive groups (p < .05). The preliminary psychometric integrity of the scales, along with continued research efforts, is an important contribution to evidence-based practice.